1983
DOI: 10.1007/bf00755411
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the utilization of outpatient mental health services

Abstract: This article describes two sets of field studies undertaken by the program evaluation unit of a community mental health center. These studies analyzed clients' utilization of service and assessed service impact in the process of testing procedural variations in service delivery. In the first set of studies, a procedure for ensuring verbal client-therapist contact prior to the first appointment was developed and tested. This procedure reduced the no-show rate for initial appointments from 22 to 12%. In the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 28 publications
1
42
1
Order By: Relevance
“…Attrition, dropout, and retention rates are a complex issue and confound researchers, clinical providers and organizational administrators alike (Larsen et al 1983;Kazdin et al 1995). Inconsistent findings in the literature are in part due to how the term dropout is defined and at what stage in the clinical process attrition occurs.…”
Section: Discussionmentioning
confidence: 95%
“…Attrition, dropout, and retention rates are a complex issue and confound researchers, clinical providers and organizational administrators alike (Larsen et al 1983;Kazdin et al 1995). Inconsistent findings in the literature are in part due to how the term dropout is defined and at what stage in the clinical process attrition occurs.…”
Section: Discussionmentioning
confidence: 95%
“…Deane et al (1992) found that a brief preparational videotape improved client knowledge about therapy and reduced anxiety but showed no improvements on therapeutic outcomes. However, others have found that prepared clients reported greater symptom reduction and lower rates of attrition than a group without the intervention (Larsen, Nguyen, Green, & Attkisson, 1983), a greater decrease in selfreported symptoms (Zwick & Attkisson, 1985), significantly more accurate expectations, and decreased state and trait anxiety (Douglas, Noble, & Newman, 1999).…”
Section: Effectiveness Of Preparatory Educational Interventions For Pmentioning
confidence: 95%
“…Specifically, attrition decreases the validity of the inferences that can be drawn about treatment efficacy, as it can alter random composition of groups, reduce statistical power, limit the generality of findings, and introduce sampling bias (Armbruster & Kazdin, 1994). Second, premature treatment termination has a negative financial impact on the mental health service system by decreasing cost-effectiveness, as missed and cancelled appointments decrease staff productivity and cause an increase in unit cost for services (Garfield, 1994;Larsen, Nguyen, Green, & Attkisson, 1983;Pekarik, 1985). These problems have led some to identify poor treatment attendance as the most important issue facing psychotherapy researchers (e.g., Phillips, 1985).…”
Section: Treatment Attendancementioning
confidence: 98%